Machinability and surface integrity investigation during helical hole milling in AZ31 magnesium alloy - Raviraja Adhikari; Gururaj Bolar; Ragavanantham Shanmugam; Ugur Koklu (International Journal of Lightweight Materials and Manufacture, 2023)
Conventional drilling has been widely used for making holes in structural materials. However, drawbacks like high cutting forces, poor surface finish, high cutting temperatures, excessive tool wear, and undesirable burr formation while drilling magnesium alloys have necessitated the development of alternative hole-making methods. Lately, the helical milling process has attracted interest in facilitating hole-making for assembly applications. However, the machinability of magnesium alloys using the helical milling process needs more investigation. Therefore, the presented work analyzed the influence of axial pitch, tangential feed, and spindle speed on cutting forces and surface integrity while milling AZ31 magnesium alloy. Axial feed was the most crucial factor contributing to the thrust force (71.8%), followed by tangential feed (13.2%). All three process variables impacted the radial force. Spindle speed was the most influential variable affecting the surface roughness (48.7%), followed by axial pitch (31.4%) and tangential feed (12.5%). Microhardness closer to the free surface of the hole was higher than the subsurface hardness. Moreover, microhardness showed an upward trend with the rise in axial pitch and tangential feed; however, it reduced with increased spindle speed.